Mitochondrial DNA quantification correlates with the developmental potential of human euploid blastocysts but not with that of mosaic blastocysts - Wen Luo; Yi-Min Zheng; Yan Hao; Ying Zhang; Ping Zhou; Zhaolian Wei; Yunxia Cao; Dawei Chen (BMC, 2023)
Abstract Purpose We aimed to study the association between adjusted mtDNA levels in human trophectoderm biopsy samples and the developmental potential of euploid and mosaic blastocysts. Methods We analyzed relative mtDNA levels in 2,814 blastocysts obtained from 576 couples undergoing preimplantation genetic testing for aneuploidy from June 2018 to June 2021. All patients underwent in vitro fertilization in a single clinic; the study was blinded-mtDNA content was unknown at the time of single embryo transfer. The fate of the euploid or mosaic embryos transferred was compared with mtDNA levels. Results Euploid embryos had lower mtDNA than aneuploid and mosaic embryos. Embryos biopsied on Day 5 had higher mtDNA than those biopsied on Day 6. No difference was detected in mtDNA scores between embryos derived from oocytes of different maternal ages. Linear mixed model suggested that blastulation rate was associated with mtDNA score. Moreover, the specific next-generation sequencing platform used have a significant effect on the observed mtDNA content. Euploid embryos with higher mtDNA content presented significantly higher miscarriage rates and lower live birth rates, while no significant difference was observed in the mosaic cohort. Conclusion Our results will aid in improving methods for analyzing the association between mtDNA level and blastocyst viability.